Comorbid disease drives short-term hospitalization outcomes in patients with multiple sclerosis. Issue 3 (June 2020) - Mendizabal, Adys; Thibault, Dylan P.; Crispo, James A.; Paley, Adina; Willis, Allison W.
Abstract : Objective: Readmission is used as a quality indicator and is the primary target outcome for disease-modifying therapy (DMT) for multiple sclerosis (MS). However, data on readmissions for patients with MS are limited. Methods: Using the US Nationwide Readmissions Database, we performed a retrospective cohort study of adults hospitalized for MS in 2014. Primary study outcomes were within 30- and 90-day readmissions. Descriptive analyses compared patient, clinical, and hospital variables readmission status. Multivariable logistic regression models estimated the associations between these variables and readmission. Results: Of 16, 629 individuals meeting the study criteria, most were women (73.7%), aged 35–54 years (48.0%), and Medicare program participants (36.8%). In total, 49.7% of inpatients with MS had 1–2 comorbid medical conditions and 23.7% had 3 or more. Having 3 or more comorbidity conditions associated with increased adjusted odds of the 30-day readmission (adjusted odds ratio [AOR] 1.92, 1.34–2.74). Anemia (AOR 1.62, 1.22–2.14), rheumatoid arthritis/collagen vascular diseases (AOR 2.20, 1.45–3.33), congestive heart failure (AOR 2.43, 1.39–4.24), chronic pulmonary disease (AOR 1.35, 1.02–1.78), diabetes with complications (AOR 2.27, 1.45–3.56), hypertension (AOR 1.25, 1.03–1.53), obesity (AOR 1.35, 1.05–1.73), and renal failure (AOR 1.68, 1.06–2.67) were associated with the 30-day readmission. Medicare insurance and nonroutine discharge were also associated with readmission, whereas patient characteristics (sex, age, and socioeconomic status) were not. The most frequent (26.7%) reason for readmission was multiple sclerosis. Ninety-day analyses produced similar findings. Conclusions: Comorbid diseases were associated with the readmission for persons with multiple sclerosis. Evaluations of the real-world effectiveness for DMTs in reducing hospitalizations in patients with MS may need to consider comorbid disease burden and management.